Export quality in advanced and developing economies: Evidence from a new dataset - Christian Henn; Chris Papageorgiou; Nikolas Spatafora (World Trade Organization (WTO), 2015)
This paper develops new estimates of export quality, far more extensive than previous efforts, covering 178 countries and hundreds of products during the period 1962-2010. It finds that quality upgrading is particularly rapid during the early stages of development, with the process largely completed as a country reaches upper middle-income status. There is significant crosscountry heterogeneity in the growth rate of quality. Within any given product line, quality converges over time to the world frontier. Institutional quality, liberal trade policies, FDI inflows, and human capital all promote quality upgrading, although their impact varies across sectors. The results suggest that reducing barriers to entry into new sectors can allow economies to benefit from rapid quality convergence over time.
Keywords: F14; L15; O11; O14; 330; Volumes; Export prices; Quality ladders; Upgrading; Sector development